Understanding the Performance: Learning Identity and Domestic Violence - Heather Nash Boxler (Adult Education Research Conference, 2004)
This interpretive ethnographic study examines the process of learning identity as it relates to domestic violence. An identity construct that includes a sense of self and a sense of social is described. Changes are traced in survivors’ identities over time.